Topographical connections of the substantia nigra pars reticulata to higher-order thalamic nuclei in the rat - ONAT, FİLİZ; YANANLI, HASAN RACİ; GÜLÇEBİ İDRİZ OĞLU, MEDİNE (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
The substantia nigra pars reticulata (SNR) is the ventral subdivision of the substantia nigra and contains mostly GABAergic neurons. The present study explores whether the SNR relates to all dorsal thalamic nuclei equally or just to a particular group of nuclei, such as first or higher-order nuclei. Injections of biotinylated dextran amine (BDA) were made into the SNR of 10 male adult rats. The distribution of anterogradely labelled axon terminals in the thalamic nuclei was documented. The projections of the SNR to the thalamic nuclei were exclusively to some motor higher-order, but not to first-order thalamic relays. There were bilateral projections to the ventromedial (VM), parafascicular (PF), centromedian (CM) and paracentral (PC) nuclei and unilateral projections to the centrolateral (CL), mediodorsal (MD) and thalamic reticular nucleus (Rt). Labelled axon terminals in the thalamic nuclei ranged from numerous to sparse in VM, PF, CM, CL, PC, MD and Rt. Further, injections into the SNR along its rostral-caudal axis showed specific topographical connections with the thalamic nuclei. The rostral SNR injections showed labelled axon terminals of VM, PF, CL, PC, CM, MD and Rt. Caudal SNR injections showed labelling of VM, PF, PC, CM and MD. All injections showed labelled axons and terminals in the zona incerta. The nigrothalamic GABAergic neurons can be regarded as an important system for the regulation of motor activities. The SNR is in a position to influence large areas of the neocortex by modulating some of the motor higher-order thalamic nuclei directly or indirectly via Rt. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Thalamus; Substantia nigra pars reticulata; Higher-order; Anterograde tracing; BASAL GANGLIA; CORTICOTHALAMIC PROJECTIONS; DEVELOPMENTAL REGULATION; LATERAL GENICULATE; PREFRONTAL CORTEX; NEURONS; ORGANIZATION; INNERVATION; 1ST-ORDER; INPUT